Perkiraan harga saham pada perusahaan aneka tambang dengan metode double exponential smoothing - Fadillah Nasution, Rizky; Rafidah, Rafidah; Mubarak, Fadhlul (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
This study discusses forecasting using quantitative research methods that aim to apply time series charts to Aneka Tambang company stocks. The right guess is vert information needed by investors in determining the next strategy in investing, which is the Double Exponential Smoothing method. This method is a time series method used to predict the future using historical data. Giving weights involves a period, so the longer the period we use, the less weighting the last value we use. With the availability of existing data, a system is formed that utilizes past data where the time series model tries to use the past time series to predict, later the system is useful to assist investors in predicting estimates of the magnitude of the value in the future so that they can determine the right strategy for investment